Altered Renal Vascular Responsiveness to Vasoactive Agents in Rats with Angiotensin II-Dependent Hypertension and Congestive Heart Failure - Vacková, Šárka; Kikerlová, Soňa; Melenovsky, Vojtěch; Kolář, František; Imig, John D; Kompanowska-Jezierska, Elzbieta; Sadowski, Janusz; Červenka, Luděk (Kidney & blood pressure research, 2019)
OBJECTIVE: We evaluated the hypothesis that the development of renal dysfunction and congestive heart failure (CHF) caused by volume overload in rats with angiotensin II (ANG II)-dependent hypertension is associated with altered renal vascular responsiveness to ANG II and to epoxyeicosatrienoic acids (EETs). METHODS: Ren-2 transgenic rats (TGRs) were used as a model of ANG II-dependent hypertension. CHF was induced by volume overload achieved by the creation of the aorto-caval fistula (ACF). Renal blood flow (RBF) responses were determined to renal arterial administration of ANG II, native 11,12-EET, an analog of 14,15-EETs (EET-A), norepinephrine (NE), acetylcholine (Ach) and bradykinin (Bk) in healthy (i.e., sham-operated) TGR and ACF TGR (5 weeks after ACF creation). RESULTS: Selective intrarenal administration of neither vasoactive drug altered mean arterial pressure in any group. Administration of ANG II caused greater decreases in RBF in ACF TGR than in sham-operated TGR, whereas after administration of NE the respective decreases were comparable in the 2 groups. Administration of Ach and Bk elicited significantly higher RBF increases in ACF TGR as compared with sham-operated TGR. In contrast, administration of 11,12-EET and EET-A caused significantly smaller RBF increases in ACF TGR than in sham-operated TGR. CONCLUSION: The findings show that 5 weeks after creation of ACF, the TGR exhibit exaggerated renal vasoconstrictor responses to ANG II and reduced renal vasodilatory responses to EETs, suggesting that both these alterations might play an important role in the development of renal dysfunction in this model of CHF.
Keywords: vazokonstrikce; Rats; angiotensin II; Acetylcholine; arteria pulmonalis; Epoxyeicosatrienoic acid; Bradykinin; Hypertension; renální oběh; vazokonstriktory; Vasoconstriction; Congestive heart failure; Vasodilation; krysa rodu Rattus; Rats, Transgenic; Pulmonary Artery; Aorto-caval fistula; zvířata; Renal Circulation; Angiotensin II; vazodilatace; srdeční selhání; hypertenze; Renal dysfunction; Arterio-Arterial Fistula; Vasoconstrictor Agents; potkani transgenní; Renal blood flow; arterioarteriální píštěl; Renal vascular reactivity; Norepinephrine; Heart Failure; Animals